Awakening songs for the church, sunday school and evangelistic services - GABRIEL, Chas. H. (ed.) (Monon Building)
Just outside the door/ B.D. AckleynOnly a sinner/ D.B. TownernCan the world see jesus in you/ C.H. MorrisnJesus of calvary/ Jas J. BellnWonderful power/ Chas H. Gabriel